2016
DOI: 10.1097/jom.0000000000000672
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Function in Latino Farmworkers

Abstract: Objectives We compared olfactory function in pesticide-exposed Latino farmworkers and non-farmworkers to explore its use as a subclinical indicator of neurological pesticide effects. Methods We recruited 304 current farmworkers and 247 non-farmworkers. All completed odor identification (14 odors) and threshold tests (16 concentrations of n-butanol) using a well-established methodology. Results Farmworkers reported significantly greater lifetime pesticide exposure. Performance on both olfactory tests declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…14 In addition, we have shown that a mixed group of male and female farmworkers demonstrate lower ability than a comparable group of non-farmworkers to detect a standard odor at a single point in time. 15 That study was unique in the occupational health literature, though the results were as expected in a population that is likely at risk for Parkinson’s disease and other neurodegenerative diseases for which decline in olfactory function is an early symptom.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…14 In addition, we have shown that a mixed group of male and female farmworkers demonstrate lower ability than a comparable group of non-farmworkers to detect a standard odor at a single point in time. 15 That study was unique in the occupational health literature, though the results were as expected in a population that is likely at risk for Parkinson’s disease and other neurodegenerative diseases for which decline in olfactory function is an early symptom.…”
Section: Introductionmentioning
confidence: 57%
“…Because no between-group differences in odor identification were found at Contact 1, 15 only odor threshold is used in the present analysis. The odor threshold test used customized “Sniffin’ Sticks” kits 16 (Burghart GmbH, Wedel, Germany) developed specifically for this study and population.…”
Section: Methodsmentioning
confidence: 99%
“…In analyses using data from other components of the PACE4 study, we have documented that pesticide exposure is related to cholinesterase inhibition 34 , impaired olfaction 35,36 and aspects of neurobehavioral function 37 . These support sub-clinical effects of OP exposure on health.…”
Section: Discussionmentioning
confidence: 99%
“…Although a direct olfactory impairment from chemical exposure including pesticides has not been identified, it is known that some environmental chemicals may induce respiratory inflammations that cause such damage (Doty, 2015). Furthermore, it has been suggested that olfactory loss can occur as a result of exposure to chemicals present in air pollution or workplace situations (Quandt et al, 2016), but no specific link between chlordane and olfactory disorders has been reported.…”
Section: Discussionmentioning
confidence: 99%